Avaliação da eficácia de um reator retangular, contínuo, com eletrodos em formato de chicanas no tratamento de efluentes oleosos por eletrocoagulação - Leite, Daniela Luz (2024)
Oily waters from various industrial sectors are effluents containing millions of liters of oil-in-water (O/W) emulsions, requiring prior treatment before disposal. Research on electrocoagulation (EC) to recover oily effluents has been highlighted. Electrolysis, a non-spontaneous reaction that releases metal into the medium, decomposes the synthetic emulsion, resulting in the formation of flakes in the medium. The flakes integrated with the gas bubbles culminate in the separation of the oil and the obtaining of the treated effluent. This research explored the rectangular geometry, applied to an EC reactor, in the search for an efficient and rapid recovery of emulsified oil in water. The influence of the volumetric flow rate and the polarity inversion time in this process were evaluated. The dependent variables include turbidity, pH, aluminum (Al) concentration, residual oil content and zeta potential. The rectangular reactor was equipped with Al electrodes arranged in the form of baffles, connected by a polarity inverter, operating in continuous mode. The best results were obtained using 2.58 mL/s in the inlet flow rate and 20 s of polarity inversion time, achieving 95.62% oil removal and 97.87% turbidity removal. The highest energy efficiency was obtained using 4 mL/s and 20 s of the parameters recently mentioned, obtaining 89.86% oil removal and 95.70% turbidity removal. The zeta potential analysis showed that the EC alters the stability of the emulsion. The pH remained within the legal requirements throughout all experiments. The wear of the plates was minimal, stipulating that their reuse can be implemented. Complementary tests indicated that the use of perforated electrodes increases the efficiency of contaminant removal, as well as indicating that the reuse of electrodes for twice the time reduced the aluminum concentration at the reactor outlet. Despite this, in all experiments the amount of aluminum obtained was higher than the current standard, indicating the need to add another step in this process, in order to retain Al3+ ions.